The CHK1 inhibitor MU380 significantly increases the sensitivity of human docetaxel-resistant prostate cancer cells to gemcitabine through the induction of mitotic catastrophe - Drápela, Stanislav; Khirsariya, Prashant; van Weerden, Wytske M; Fedr, Radek; Suchánková, Tereza; Búzová, Diana; Červený, Jan; Hampl, Aleš; Puhr, Martin; Watson, William R; Culig, Zoran; Krejčí, Lumír; et al. (Molecular oncology, 2020)
As treatment options for patients with incurable metastatic castration-resistant prostate cancer (mCRPC) are considerably limited, novel effective therapeutic options are needed. Checkpoint kinase 1 (CHK1) is a highly conserved protein kinase implicated in the DNA damage response (DDR) pathway that prevents the accumulation of DNA damage and controls regular genome duplication. CHK1 has been associated with prostate cancer (PCa) induction, progression, and lethality; hence, CHK1 inhibitors SCH900776 (also known as MK-8776) and the more effective SCH900776 analog MU380 may have clinical applications in the therapy of PCa. Synergistic induction of DNA damage with CHK1 inhibition represents a promising therapeutic approach that has been tested in many types of malignancies, but not in chemoresistant mCRPC. Here, we report that such therapeutic approach may be exploited using the synergistic action of the antimetabolite gemcitabine (GEM) and CHK1 inhibitors SCH900776 and MU380 in docetaxel-resistant (DR) mCRPC. Given the results, both CHK1 inhibitors significantly potentiated the sensitivity to GEM in a panel of chemo-naïve and matched DR PCa cell lines under 2D conditions. MU380 exhibited a stronger synergistic effect with GEM than clinical candidate SCH900776. MU380 alone or in combination with GEM significantly reduced spheroid size and increased apoptosis in all patient-derived xenograft 3D cultures, with a higher impact in DR models. Combined treatment induced premature mitosis from G1 phase resulting in the mitotic catastrophe as a prestage of apoptosis. Finally, treatment by MU380 alone, or in combination with GEM, significantly inhibited tumor growth of both PC339-DOC and PC346C-DOC xenograft models in mice. Taken together, our data suggest that metabolically robust and selective CHK1 inhibitor MU380 can bypass docetaxel resistance and improve the effectiveness of GEM in DR mCRPC models. This approach might allow for dose reduction of GEM and thereby minimize undesired toxicity and may represent a therapeutic option for patients with incurable DR mCRPC.
Keywords: Animals; Drug Resistance, Neoplasm; proliferace buněk; pyrimidiny; docetaxel; myši SCID; Cell Line, Tumor; Deoxycytidine; Checkpoint Kinase 1; Pyrazoles; lidé; pyrazoly; S Phase; chemorezistence; Docetaxel; nádory prostaty; checkpoint kinasa 1; Mice, SCID; Prostatic Neoplasms; Mitosis; buněčná smrt; mitóza; xenogenní modely - testy protinádorové aktivity; deoxycytidin; Male; Piperidines; Cell Death; Cell Proliferation; Xenograft Model Antitumor Assays; S fáze; zvířata; mužské pohlaví; piperidiny; nádorové buněčné linie; Pyrimidines; Humans